PEMANFAATAN BIJI BUAH MANGGA DAN MADU SEBAGAI BAHAN PEMBUATAN SABUN WAJAH JENIS KULIT KERING - Br Saragih S, Yuniarti; Sri Usodoningtyas (Jurnal Tata Rias, 2021)
Dry skin condition is a problem for some people and it feel uncomfortable. The indications of dry skin is a tight feeling on the skin as well as stiff, dull, rough, scaly, itching, redness to pain resulting in irritation. Therefore, it is necessary to treat dry skin. Facial soap is one of several types of skin care cosmetics. This research aims to know (1) mango seeds as facial soap to treat dry skin, (2) honey as facial soap to treat dry skin. Facial soap can treat facial skin by moisturizing the dry skin, it is the right treatment, and can minimize the error rate in choosing cosmetic care by utilizing natural ingredients that are easy and cheap found in the daily. Mango seeds are nutritious plants as antibacterial and honey to moisturize. The research is using the literature study method and observation by observing the results of previous research in collecting the data and or information for the study. Based on The results of a literature review show that mango seeds and honey are used in soap making face can moisturize and improve dry skin conditions.